Law Enforcement Officer Knowledge of Mental Illness - Funn, Nashira (2017)
Media and activist groups have recently exposed the problem of negative interactions between law enforcement officers and civilians. Many of these civilians have a mental illness. Various researchers attribute these negative interactions to insufficient officer knowledge of mental illness due to a lack of training, education, and personal experiences. Very little research addresses how insufficient knowledge of mental illness may influence interactions. The purpose of this phenomenological study was to explore and analyze self reported law enforcement knowledge using Malcolm Knowles' conceptualization of adult learning theory and andragogy as the theoretical framework. This framework bases self-directed learning/training on a needs assessment of the individual's knowledge. The main research question was: 'What factors related to officer knowledge of mental illness impact interactions between law enforcement and people with mental illness?' Data were collected through recorded and then transcribed in-depth interviews with 8 law enforcement officers with experience interacting with mentally ill people. Using aspects of modified Van Kaam method of data analysis, word recognition computer programing identified repetitive words and phrases from the data. This resulted in significant common themes, namely: the need for more effective formal training on mental illness and the influence of personal lived experiences in the interaction with people with mental illness. The implications for social change are positive for officers and people with mental illness, as this study will inform the development of more effective officer training models about mental health, which will reduce the number of negative interactions